2000
DOI: 10.1177/08861090022094038
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Single Parents and Social Injustice: A Women's Issue

Abstract: This study examined graduate social work students' perceptions of vulnerable populations. The results suggest that although the students were able to identify oppression as a factor in the lives of women and other at-risk populations, for the most part, their perceptions of single parents underscored the belief that the life conditions of femaleheaded families are the consequence of individual choice, rather than of societal arrangements that have a disproportionately negative impact on women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…In addition to these findings Ganong et al (1988) also documented negative descriptions of single mothers' morals, which included having "unconventional" attitudes and being "liberal and promiscuous" (p. 338). These results are consistent with more recent research that finds that single mothers are viewed more negatively than other groups of parents (Bennett & Jamieson, 1999;Ganong & Coleman, 1995;Rhodes & Johnson, 2000).…”
Section: Negative Societal Perceptions Of Single Motherssupporting
confidence: 95%
See 3 more Smart Citations
“…In addition to these findings Ganong et al (1988) also documented negative descriptions of single mothers' morals, which included having "unconventional" attitudes and being "liberal and promiscuous" (p. 338). These results are consistent with more recent research that finds that single mothers are viewed more negatively than other groups of parents (Bennett & Jamieson, 1999;Ganong & Coleman, 1995;Rhodes & Johnson, 2000).…”
Section: Negative Societal Perceptions Of Single Motherssupporting
confidence: 95%
“…For example, researchers examined the beliefs of undergraduate students about different types of families (i.e., remarried, married, divorced, widowed, or never-married) and found that never-married parents were perceived less positively than all of the other groups of parents (Bryan, Coleman, Ganong, & Bryan, 1986). Furthermore, Rhodes and Johnson (2000) studied societal perceptions that are held about marginalized groups of individuals (e.g., people of color, women, and single parents) using a sample of social work graduate students. These researchers found that students perceived that each of the groups experienced oppression with the exception of single parents.…”
Section: Negative Perceptions Of Single Parentsmentioning
confidence: 98%
See 2 more Smart Citations
“…Even when they are acting in opposition to the dominant images, mothers are penalized for their efforts. Social workers and other professionals continue to perceive lone mother families to be victims of their own choices, and thus, their interactions with single mothers are more punitive, rather than supportive (Rhodes & Johnson, 2000;Schmitz, 1998). It remains difficult to challenge the belief that problems experienced by single mothers are a result of inequitable social polices, and far easier to retain beließ that locate the problem within mothers' poor decision-making.…”
Section: Social and Economic Resourcesmentioning
confidence: 99%